2013
DOI: 10.1371/journal.pone.0056477
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Isolates of Vibrio cholerae O1 El Tor Ogawa of 2009 from Kolkata, India: Preponderance of SXT Element and Presence of Haitian ctxB Variant

Abstract: BackgroundIncrease in the number of multidrug resistant pathogens and the accompanied rise in case fatality rates has hampered the treatment of many infectious diseases including cholera. Unraveling the mechanisms responsible for multidrug resistance in the clinical isolates of Vibrio cholerae would help in understanding evolution of these pathogenic bacteria and their epidemic potential. This study was carried out to identify genetic factors responsible for multiple drug resistance in clinical isolates of Vib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…The HCT-producing variants of V. cholerae were reported for the first time from the cholera outbreak in Odisha during 2007, later from Haiti during 2010, and subsequently from Asia and Africa (15,16). A few reports have described the isolation of HCT-producing variant V. cholerae O1 strain or the identification of this strain as the causative pathogen of small outbreaks from West Bengal, Bihar, and southern India (6,13,14). There have been similar reports on the isolation of HCT-producing V. cholerae from Zambia (11) and from Mexico during the 2013 cholera outbreak (12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The HCT-producing variants of V. cholerae were reported for the first time from the cholera outbreak in Odisha during 2007, later from Haiti during 2010, and subsequently from Asia and Africa (15,16). A few reports have described the isolation of HCT-producing variant V. cholerae O1 strain or the identification of this strain as the causative pathogen of small outbreaks from West Bengal, Bihar, and southern India (6,13,14). There have been similar reports on the isolation of HCT-producing V. cholerae from Zambia (11) and from Mexico during the 2013 cholera outbreak (12).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, new ctxB genotypes were observed in Zambia and Mexico during 2013, which represent variants of ctxB7 in HCT-producing V. cholerae (11,12). The ctxB7 variant V. cholerae O1 was first reported from the tribal areas of Odisha, India, during 2007 (6,13). These HCT variant strains of V. cholerae O1 were also reported from the Maharashtra (14) and Bihar states of India during 2012 (15).…”
Section: Introductionmentioning
confidence: 92%
“…Resistance to fluoroquinolones has been reported in studies from India [10], however most of the isolates were found to be susceptible to fluoroquinolones (Norfloxacin) in the present study. A number of multidrug resistance strains are also emerging in clinical isolates of V. cholera 01; serotype Ogawa, including resistance to trimethoprim-sulphamethoxazole and ampicillin [11]. Other studies have showed the current emerging toxigenic Inaba strains of Eltor biotype, than the earlier classical biotype [12].…”
Section: Discussionmentioning
confidence: 99%
“…The AET strains have a gyrA mutation for nalidixic acid resistance and integrating conjugative elements (ICE) that confer multiple drug resistance, including to streptomycin and chloramphenicol (3,7,8). The ICEVchIn5 present in ϳ77% of strains has recently been shown to also encode a repressor of V. cholerae natural competence (9,10).…”
mentioning
confidence: 99%
“…This clonal variant of V. cholerae with tcpA N89S , rtxA°, and ctxB7 alleles was first detected in Kolkata, India, in 2004 (7). It was also identified as the cause of outbreaks in Orissa, India, in 2007 (19), in Cameroon, Zimbabwe, and South Africa in 2009, and in Nepal in 2010 (8,13,14,18). The strain has been the predominant cause of cholera in India and Bangladesh at least to 2012 (7,20,21).…”
mentioning
confidence: 99%